2018
DOI: 10.1111/jmwh.12684
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Implementing Group‐Level Prenatal Health Interventions in Low‐Resource Communities: Lessons Learned From Haiti

Abstract: Haiti's high maternal and infant mortality rates evidence an urgent need for implementation of evidence-based strategies. A potential cost-effective strategy to mitigate high maternal and infant mortality rates is group prenatal care, an innovative model that combines antenatal clinical assessment with pregnancy education. Despite research demonstrating the effectiveness of this model in high-resource settings, less is known about the challenges of implementing it in low-resource settings. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
10
1
6
Order By: Relevance
“…In contrast with our findings, literature in low‐income settings has focused on culture change and implementing group antenatal care models in the context of foreign health care providers leading groups . In Mexico, the same people who normally work in the facilities led all group antenatal care sessions; the Mexican research team was present during sessions but did not facilitate them.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…In contrast with our findings, literature in low‐income settings has focused on culture change and implementing group antenatal care models in the context of foreign health care providers leading groups . In Mexico, the same people who normally work in the facilities led all group antenatal care sessions; the Mexican research team was present during sessions but did not facilitate them.…”
Section: Discussioncontrasting
confidence: 95%
“…The decision was made to hold sessions in a diverse set of conveniently accessible, shared public locations. Running groups outside clinics posed several challenges, including high temperatures and concerns about women's comfort, as well as confidentiality …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While little research exists on group ANC in low- and middle-income countries, several studies have shown the feasibility of delivering group ANC in these settings [26, 27]. Challenges to implementing group ANC in a low resource setting (Haiti) have been described and include space, literacy, language, and cultural appropriateness of content [31]. While this is not the focus of this article, the description of the process of adaptation and implementation are described elsewhere [26, 28].…”
Section: Discussionmentioning
confidence: 99%